The DMGT: Changes within, beneath, and beyond - Gagne, F. (Talent Development & Excellence, 2013)
This article begins with a brief survey of the recent update of the Differentiating Model of Giftedness and Talent (DMGT). The DMGT defines talent development as the transformation of outstanding natural abilities (called gifts-G) into outstanding knowledge and skills (called talents-T). Two types of catalysts, intrapersonal (I) and environmental (E), actively moderate the talent development process (D). These causal components of talent development have biological underpinnings; I propose here a way to integrate these biological roots to the DMGT in the form of `basements` that exert their influence upwards to moderate the development of natural abilities, as well as many intrapersonal catalysts like temperament, needs, interests, and volition. This new tri-dimensional approach to the structure of talent development leads to two hitherto unpublished proposals. The first one is a Developmental Model for Natural Abilities (DMNA), in which biological building blocks create a diversity of natural abilities, through a developmental process based on maturation and informal learning, and with the necessary contribution of both sets of I and E catalysts. The second one integrates the new DMNA and the DMGT into an Expanded Model of Talent Development (EMTD) that begins with the biological foundations and ends with high level expertise.